Efektivitas Pembelajaran Team Games Tournament berbantuan ULTADU terhadap Kemampuan Pemecahan Masalah Siswa Kelas V - Anggita Aulia Alifiani; Hesti Yunitiara Rizqi (JANACITTA, 2025)
Abstract  This research is based on students low problem solving ability. One effort to improve the situation is by using the model Team Games Tournament. The aim of the research was to investigate the effectiveness of the Team Games Tournament model on students' problem solving abilities with the help of ULTADU (Educational Snakes Ladders) in class V students at SDN Sidomulyo 04. The type of research used was a quasi-experiment with a non-equivalent control group research design by providing pre-test and final post-test abilities. The instruments used in this research were tests and non-tests.  The sample chosen in this research was the VA class with 25 students and the VB class with 25 students. The experimental class VB was treated using the Team Games Tournament model with the help of ULTADU. The control class VA was given treatment using the Team Games Tournament model without the help of learning media. The research results showed that the average problem solving ability of the experimental class was 77.04 percentage of success (71%) while the average problem solving ability of the control class was 68.48 percentage of success (68%), the average problem solving ability of the experimental class was better than the control class and the percentage of success of the experimental class was better than the control class. Thus, it can be concluded that the TGT learning model assisted by ULTADU is effective on the problem solving abilities of  grade V elementary school students.  Abstrak                                                                                         Penelitian ini dasari oleh rendahnya kemampuan pemecahan masalah siswa. Salah satu upaya untuk memperbaiki keadaan dengan menggunakan model Team Games Tournament. Tujuan penelitian untuk menyelidiki keefektifan model Team Games Tournament terhadap kemampuan pemecahan masalah siswa berbantuan ULTADU (Ular Tangga Edukatif) pada siswa kelas V SDN Sidomulyo 04. Jenis penelitian yang dipakai adalah quasi eksperimen dengan desain penelitian non equivalent control grup design dengan memberikan kemampuan tes awal pretest dan tes akhir posttest. Instrumen yang digunakan dalam penelitian ini adalah tes dan non tes.  Sample yang dipilih dalam penelitian ini adalah kelas VA berjumlah 25 siswa dan kelas VB berjumlah 25 siswa. Kelas eksperimen VB diberi perlakuan menerapkan model Team Games Tournament berbantuan ULTADU kelas kontrol VA diberi perlakuan menerapkan model Team Games Tournament tanpa berbantuan media pembelajaran. Hasil penelitian menunjukkan bahwa rata – rata kemampuan pemecahan masalah kelas eksperimen 77,04 persentase keberhasilan (71%)  sedangkan rata – rata kemampuan pemecahan masalah kelas kontrol 68,48 persentase keberhasilan (68%), rata – rata kemampuan pemecahan masalah kelas eksperimen lebih baik dari kelas kontrol serta persentase keberhasilan kelas eksperimen lebih baik dari kelas kontrol. Dengan demikian, dapat disimpulkan bahwa model pembelajaran Team Games Tournament berbantuan ULTADU efektif terhadap kemampuan pemecahan masalah siswa kelas V Sekolah Dasar.